Pengambilan Keputusan Pembelian Kue Pisang Berdasarkan Komunikasi Pemasaran, Inovasi Produk, dan Harga - Ida Rosada; Nurliani; A. Asrarul Amri; Akda Saktiyandi Asrul (Jurnal Galung Tropika, 2025)
Rapid business development has given rise to tight market competition. Every day business people appear to introduce products with new creativity and innovation. One of the snacks offered on the market is brownies with the brand "Browcyl". The research objectives are: 1) Describe variants, prices and sales volumes 2) Analyze consumer perceptions of marketing communications, product innovation and prices 3) Analyze purchasing decision making. 4) Analyze the influence of marketing communications, product innovation, and price on purchasing decision making. The population is consumers who buy directly. The sampling technique was purposive with a total of 50 respondents. Data analysis is descriptive and multiple linear regression. Research results: 1) The product type consists of 8 variants, namely: original unti, choco almond, pandan, cheese, tiramisu, cheesecream, chocolate flan, and moccaramel. The price for Browcyl banana brownies ranges from IDR 50,000 – IDR 68,000. The total sales volume during April–August 2023 averages 308 pcs. 2) Consumer perceptions of marketing communications, product innovation and high category prices. 3) Purchasing decisions consisting of 5 stages, namely, problem/need recognition, information search, alternative evaluation, purchasing decisions and high category post-purchase behavior. 4) The marketing communication variables, product innovation and price on the purchasing decision making process have a very significant effect simultaneously and partially.